TAM Plasticity under androgen deprivation therapy and PARP inhibition in prostate cancer: a multi-omics perspective - Chen, Shuangming; Cai, Weiwei; Liu, Chunlin (Frontiers in Immunology, 2025)
Androgen deprivation therapy (ADT) and next-generation androgen receptor pathway inhibitors (ARPI) are increasingly combined with PARP inhibitors (PARPi) in metastatic prostate cancer (mPCa). These treatments have improved outcomes, yet responses remain variable and often lack durability. Single-cell and spatial multi-omics studies indicate that tumor-associated macrophages (TAMs) strongly influence therapeutic response and form a treatment-shaped continuum of states enriched for TREM2 and SPP1 programs, lipid metabolic activity, hypoxia adaptation, and phagocytic checkpoint signaling within the osteogenic cancer-associated fibroblast (CAF) niche. Macrophages also possess functional androgen receptor (AR) activity, which supports an AR-driven myeloid circuit that promotes immune exclusion during ADT or ARPI therapy. PARP inhibitors stimulate cGAS-STING and induce senescence-associated secretory phenotypes (SASP), leading to an initial type I interferon (IFN) response that ultimately transitions to an MDSC-like immunosuppressive phenotype. These processes converge on common mechanisms of phagocytic control through CD47-SIRPα, MerTK, Axl, CSF1R, and TREM2 and represent therapeutic targets for combination therapies. This review details the combined impact of ADT and PARPi and introduces a multi-omic framework that integrates TREM2 or SPP1 burden, STING activation status, phagocytic checkpoint expression, and HRR or SPOP genotype into a Myeloid Lymphatic Composite Score (MLCS). The MLCS is a scoring tool to assist in timing and selecting therapeutic combinations of ARPI with TREM2 or CSF1R blockade, PARPi with STING modulation, and ARPI with anti-CD47 therapy. Integrating mechanistic and translational data provides a foundation for biomarker-guided regimens capable of converting prostate cancer from an immune-cold disease to an immune-responsive state.